2009
DOI: 10.1158/0008-5472.sabcs-56
|View full text |Cite
|
Sign up to set email alerts
|

c-MYC amplification and correlation with patient outcome in early stage HER2+ breast cancer from the NCCTG adjuvant intergroup trial N9831.

Abstract: #56 Background: Recent findings from NSABP B-31 suggested that breast cancer (BC) patients (pts) with c-MYC (MYC)/HER2 co-amplification in their primary tumors may benefit more in terms of disease-free survival (DFS) from adjuvant trastuzumab (n=471; p<0.0001, HR 0.24; 13 vs. 51 events) than those pts with only HER2 amplification in their primary tumors (n=1078, p=0.007, HR 0.63; 55 vs. 82 events).
 Purpose: The overall objective of this analysis is to determine the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A mean score for MYC, CEP8 and the MYC/CEP8 ratio was calculated. Using the criteria of Perez et al, 82 an MYC/CEP8 ratio of 41.3 or a mean tumour cell MYC copy number of 45 was used to determine cases with MYC amplification.…”
Section: Patientsmentioning
confidence: 99%
“…A mean score for MYC, CEP8 and the MYC/CEP8 ratio was calculated. Using the criteria of Perez et al, 82 an MYC/CEP8 ratio of 41.3 or a mean tumour cell MYC copy number of 45 was used to determine cases with MYC amplification.…”
Section: Patientsmentioning
confidence: 99%
“…[1][2][3][4] However, many women who receive trastuzumab develop resistance within 1 year, and 15% to 25% of women diagnosed with HER2-positive, early-stage disease develop tumor relapse within 3 years, despite therapy. 5 Thus, identifying patients who would respond best to trastuzumab is critical to the appropriate management of patients with HER2-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 MYC, located on chromosome 8, is a proto-oncogene with a central role in proliferation and malignant transformation of human and animal cells. 8 Its protein product (MYC) is a transcription factor that critically participates in most aspects of normal cellular function, including replication, proliferation, metabolism, differentiation, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report showed that c-MYC may be candidate molecule to select for trastuzumab therapy, because of increased responsiveness. Perez et al [23] corroborated that c-MYC amplification is not associated with added benefit to trastuzumab treatment in the N9831 trial (a global study using adjuvant trastuzumab). As yet, there are no confirmed molecules for individualized adjuvant treatment in HER2-positive breast cancer.…”
Section: Small Tumorsmentioning
confidence: 95%